2001
DOI: 10.1074/jbc.c100154200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Na+/H+ Exchanger Regulatory Factor PDZ1 Interaction with the Carboxyl-terminal Region of the Cystic Fibrosis Transmembrane Conductance Regulator

Abstract: The PDZ1 domain of the Na ؉ /H؉ exchanger regulatory factor (NHERF) binds with nanomolar affinity to the carboxyl-terminal sequence QDTRL of the cystic fibrosis transmembrane conductance regulator (CFTR) and plays a central role in the cellular localization and physiological regulation of this chloride channel. The crystal structure of human NHERF PDZ1 bound to the carboxyl-terminal peptide QDTRL has been determined at 1.7-Å resolution. The structure reveals the specificity and affinity determinants of the PDZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
136
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 40 publications
16
136
0
Order By: Relevance
“…The C-terminal residue of the peptide ligand is accommodated in a pocket created by an ␣-helix (B), the B strand, and a conserved GLGF loop connecting the A and B strands, whereas the serine or threonine residue at the Ϫ2 position forms an essential hydrogen bond with a conserved histidine residue in helix B. These features explain the requirement for a PDZ type I binding motif, but the specificity of the interaction seems to be determined mostly by further interactions between the side chains of residues at positions Ϫ1, Ϫ3, and Ϫ4 of the peptide ligand and the PDZ domain (17,18,(21)(22)(23)(24)(25). In the present study, we did not observe any clear effects of side-chain alteration at these positions in the GluR-A subunit.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal residue of the peptide ligand is accommodated in a pocket created by an ␣-helix (B), the B strand, and a conserved GLGF loop connecting the A and B strands, whereas the serine or threonine residue at the Ϫ2 position forms an essential hydrogen bond with a conserved histidine residue in helix B. These features explain the requirement for a PDZ type I binding motif, but the specificity of the interaction seems to be determined mostly by further interactions between the side chains of residues at positions Ϫ1, Ϫ3, and Ϫ4 of the peptide ligand and the PDZ domain (17,18,(21)(22)(23)(24)(25). In the present study, we did not observe any clear effects of side-chain alteration at these positions in the GluR-A subunit.…”
Section: Discussionmentioning
confidence: 99%
“…9). Rather, we found that RACK1 and NHERF1, a scaffold protein that binds four carboxyl-terminal amino acids (DTRL) of CFTR through either of its PDZ (PDZ1 and PDZ2) domains (29,31,37,38), coimmunoprecipitate from Calu-3 cells and are binding partners (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…5A) (19,44,45). More recently, structures have been published for PDZ domains from ␣-syntrophin (22) and the H ϩ /Na ϩ exchange regulatory factor (HNERF PDZ1) (48,49), in which specific hydrophobic or hydrogen bond interactions are observed to the Ϫ1 position side chain (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%